Role of Triggering Receptor Expressed on Myeloid Cells in the Activation of Innate Immunity - V. G. Matveyeva; A. S. Golovkin; E. V. Grigoryev; A. V. Ponasenko (Общая реаниматология)
The innate immune system plays a key role in triggering a systemic inflammatory response (SIR). The triggering receptor expressed on myeloid cells (TREM-1), which is located on neutrophils and monocytes, is involved in SIR, by regulating the effector mechanisms of innate immunity. Hyperproduction of proinflammatory cytokines is a pathogenetic component of the hyperergic phase of acute systemic inflammation. The simultaneous activation of Toll-like receptors and TREM-1 increases the production of cytokines manifold. This is compensatory and adaptive, however, resulting in damage to organs and tissues during excessive production of cytokines. Key words: triggering receptor expressed on myeloid cells, Toll-like receptors, cytokines, inflammation.